Missed opportunities for DCD kidney donors: Evaluation of warm ischemic time and associated functional warm ischemic time. Issue 11 (22nd October 2019) - Law, Jeffrey; Hornby, Karen; Payne, Clare; Sener, Alp; Luke, Patrick P.
Abstract: Introduction: Many transplant centers utilize a hard cutoff of 2 hours of warm ischemic time (WIT), defined as the time from withdrawal of life‐sustaining measures to cold organ flush, to exclude donation after circulatory determination of death (DCD) kidney donation. As a result, almost a quarter of withdrawals to retrieve DCD organs fail to produce kidney transplants in Ontario. In order to assess our ability to increase organ yield, we wanted to characterize WIT and functional WIT (fWIT, time from systolic blood pressure <50 mm Hg to cold organ flush), as well as determine the time at which potential donors eventually die in those that did not become organ donors. Methods: A retrospective review of all DCD kidney donors in Ontario was performed utilizing the Trillium Gift of Life Database from April 2013 to February 2018. Results: Of 350 DCD kidney donors analyzed, 46.9% had < 0.5 hours, 51.7% between 0.5 and 2 hours, and 1.4% >2 hours of WIT. In each of these categories (WIT <0.5 hours, 0.5‐2 hours and >2 hours), the percentage of patients with fWIT <30 minutes was 100%, 94.4%, and 100%, respectively ( P  = NS). There were 106 potential donors who did not end up donating due to WIT >2 hours. Of these, 20.8% died between 2 and 4 hours, 10.4% between 4 and 6 hours, and 68.8% beyond 6 hours. Discussion: The percentage of donors with fWIT >30 minutes did not increase with increasing WIT in DCD donors that went on to donate organs. These data support assessment of waiting up to 4 hours for DCD kidney donation as long as fWIT remains low.